A study of Mandarin homophony - Huff, CL (2017)
An investigation into the distribution of homophones was conducted using a large written corpus (Da, 2007). Both tone and homophony were found to be systematically uneven, with a tendency toward clustering. Syllables with the full complement of tones have, on average, higher homophone densities than those with fewer tonally-specified syllables, indicating a beneficial role of increasing homophone density in lexical processing. Three experiments were conducted to test this hypothesis. In Experiment 1, participants were shown tonally-unspecified pinyin and asked to produce a character. Participants gave the most frequent character matching the pinyin, except when two characters of differing homophone density but similar lexical frequency were in direct competition (e.g. the two highest frequency wan characters were associated with different tones). In this case, it was found that the slightly lower frequency, but higher homophone density character was selected, indicating a facilitative role of homophone density. In Experiment 2, participants were shown tonally-specified pinyin followed by characters, and asked to judge whether the two matched. Character frequency (not the cumulative frequency of all homophones) was found to be the primary determinant of response time, with higher frequency characters responded to faster than lower frequency characters regardless of homophone density. However, increasing homophone density was found to speed responses for all frequencies. High frequency characters were always faster than low frequency characters, but low frequency characters with high homophone density were faster than low frequency characters with low homophone density. In Experiment 3, participants read aloud characters embedded in context sentences. High frequency words were more reduced (i.e. shorter in duration) than low frequency homophone mates. High frequency characters with many homophones were shorter than high frequency characters with few homophones, while the opposite held for low frequency characters.